Unseen : a novel - Slaughter, Karin, 1971- (Delacorte Press, 2013)
Sent to Macon for an undercover mission to infiltrate a drug and prostitution ring, Georgia Bureau of Investigation Agent Will Trent hides the facts about his latest assignment from his girlfriend, Sara Linton, when the stakes prove higher than any he has yet encountered.